Totalitarianism and the modern conception of politics - Halberstam, Michael, 1963- (New Haven, Conn. : Yale University Press, 1999)
"Halberstam argues that neither liberalism nor totalitarianism can be understood without the other. Liberalism reflects the modern conception of politics: a vision of society as a human construct answering to an unprecedented valorization of freedom. The liberal attempt to emancipate politics from culture, however, risks a loss of shared meaning that totalitarianism promises to repair. The author thus reveals how the idea of totalitarianism embodies truths and contradictions about liberalism itself. The philosophical heart of the book is a critical development of Immanuel Kant's theory of reflective, aesthetic judgment, exposing the limits of reason and taking up what Hannah Arendt's unfinished work suggests. This rich study in the history of modern political thought from Hobbes through Marx to the present culminates with a new and surprising interpretation of Arendt's theory of totalitarianism."--Jacket
Society as artifact -- Social reconstruction and the problem of meaning -- Liberalism versus totalitarianism -- Freedom, common sense, and the limited reach of reason -- The indeterminacy of Kant's rational reason and the intervention of taste -- Totalitarianism as the liberal nightmare -- Modernity and the loss of world -- Terrible freedom.
"This book grew out of my dissertation work with Karsten Harries at Yale University"--Acknowledgments
Includes bibliographical references (pages 211-277) and index.
Print version record.
English.
JSTOR
Keywords: Totalitarianism; Totalitarisme; totalitarianism; POLITICAL SCIENCE -- General; PHILOSOPHY -- Political; Totalitarianism